The Proposal of the Examination Credits Granting Procedure According to the PART 66 - Hůlek, David; Řeha, David; Zharkova, Victoria; Novák, Martin (Kaunas University of Technology, 2020)
This article deals with the proposal of the examination credits granting procedure for aircraft maintenance technicians based on educational attainment. Regulations enable us to grant some of the theoretical exams. Otherwise, the technician must pass these exams via written tests. The first part of the article is about descriptions of the topic and the current situation in the Czech Republic. The second part, which also is the main part, is about the proposal of the credits granting procedure itself. There is a detailed description of the procedure together with a flowchart, and a description of procedure processes in this part. The last part is about a discussion and summarizing of the proposed procedure. The goal of this article is not to criticize national or European aviation authorities but an effort to unify the EU regulations implementing in all member states. The authors react to a situation that occurred in the first quarter of the year 2020 in the CZ. They try to find a solution that would be acceptable by all affected parties.
Návrh postupu pro udělení zápočtů zkoušek podle ČÁSTI 66
Keywords: examination granting; modules granting; PART 66; maintenance technician exams; theoretical exams; examination credits; uznávání zkoušek; uznání modulů; ČÁST 66; zkoušky techniků údržby; teoretické zkoušky; zápočty zkoušek